IT-BISA on English proficiency and digital literacy skills: Delving into students’ views and teacher’s reflections - Didit Kurniadi; Issy Yuliasri; Sri Wahyuni; Zulfa Sakhiyya (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
This study introduces IT-BISA (IT-Based Integrated Skills Approach), an innovative pedagogical approach to improve EFL university students’ English proficiency and digital literacy. IT-BISA integrates all four language skills with digital tools, creating a learning environment that supports language development and digital competence. This study aims to explore how IT-BISA was implemented in a TEFL course and examine its perceived impact from both the teacher’s and students’ perspectives. A qualitative research design included students’ views and the teacher’s reflective journals (early, middle, and end-of-semester). While simple percentage data were used to describe student responses, the primary analysis involved thematic analysis of reflections and survey comments. The findings revealed that 86% of students reported improvement in speaking confidence, 80% perceived progress in reading comprehension, and 90% indicated increased ability to use digital tools for academic purposes. Additionally, 88% described the learning experience as engaging and motivating. The students showed notable growth in English proficiency and confidence, particularly in speaking and reading. Moreover, their ability to use digital tools for learning also improved. Students viewed the IT-BISA-based learning as engaging, practical, and motivating. Thematic findings further reveal increased classroom interaction, stronger learner agency, and greater responsibility for independent learning. Teacher reflections also identified challenges related to technological adaptation and varying levels of digital readiness. The approach contributes to ongoing conversations about meaningful technology integration and an integrated skills approach in language education.